Impact of climate change on surface water resources - هادی, د.هادی نیری; حمەامین, د.دڵپاک احمد حمەامین; رحیمی, د.حمید رحیمی (Sulaimani Journal for Humanities, 2025)
Global warming, rising temperatures, and decreased rainfall are among the most observed signs of climate change that have dangerous impacts on human life and natural organisms. The effects of climate change, especially in recent decades, have left serious traces in regions featured by dry and semi-dry climatic conditions. The Garmian region, which falls within the semi-dry and semi-humid zone relative to the Kurdistan Region's position, has not been exempt from the apparent impacts of climate change on many environmental aspects, especially on water resources. Rising temperatures and decreased rainfall have had significant effects on the region's water resources, both in terms of size and quantity reduction, as well as the deterioration of water quality in water sources. The aim of the Current study is to determine the impact of climatic parameters, especially temperature over several decades in the Garmian region, and their impacts on discharge and water flow rates of rivers in the region. Apart from this, using satellite data and several indicators, including the NDWI index specific to analyzing the state of changes in water level and reflection, along with using 23 climate models under the moderate scenario SSP2-4.5. The study's findings showed that during the past periods 2001-2025, the NDWI index trend has been declining and negative, and the region's surface water has been in a state of reduction and declining levels. Surface water content in this scenario is expected to have a negative trend and decline up to 70 % (minimum index in the past period -0.5 and forecast period -0.7).
Keywords: Climate change; water resources; satellite data; NDWI; Climate models